Ответы и объяснения

LANAOVICH
sedinalana
LANAOVICH

А)f°(x)= 2*2x-4=4x-4  ⇒ f°(-1)= 4*(-1)-4=-4-4=-8
б)
f°(x)=(2x)*(x²+1)+(x²-1)*2x=2x³++2x+2x³-2x=4x³;)f°(1)=4·(1)³=4·1=4
в)
f°(x)=8·sinx+8x·cosx=8(sinx+x·cosx);          
f°(π/4)=8(sin(π/4)+(π/4)·cos(π/4))=8·(√2/2 +(π/4)·√2/2)=(8√2/2)·(1+π/4)=4√2·(1+π/4)=4√2+π√2
г)
f°(x) =(2x·(1+x)-x²·1)/(1+x)²=(2x+2x²-x²)/(1+x)²=(2x+x²)/(1+x)²=x(2+x)/(1+x)²            
f°(1)=1·(2+1)/(1+1)² = 1·3/2²=3/4
Вместо значка °  читать (и писать!) значок производной.

3.0
1 оценка
1 оценка
Оцени!
Оцени!
sedinalana

а

f`(x)=4x-4

f`(-1)=-4-4=-8

б

f`(x)=2x(x²+1)+2x(x²-1)=2x³+2x+2x³-2x=4x³

f`(1)=4*1=4

в

f`(x)=8sinx+8x*cosx

f`(x)=8*√2/2+8*π/4*√2/2=4√2+π√2=√2(4+π)

г

f`(x)=(2x(x+1)-1*x²)/(x+1)²=(2x²+2x-x²)/(1+x)²=(x²+2x)/(1+x)²

f`(1)=(1+2)/(1+1)²=3/4


0.0
0 оценок
0 оценок
Оцени!
Оцени!